Increasing the Frequency and Timeliness of Pain Assessment and Management in Long-Term Care: Knowledge Transfer and Sustained Implementation. (3rd March 2016) - Hadjistavropoulos, Thomas; Williams, Jaime; Kaasalainen, Sharon; Hunter, Paulette V.; Savoie, Maryse L.; Wickson-Griffiths, Abigail
Abstract : Background . Although feasible protocols for pain assessment and management in long-term care (LTC) have been developed, these have not been implemented on a large-scale basis. Objective . To implement a program of regular pain assessment in two LTC facilities, using implementation science principles, and to evaluate the process and success of doing so. Methods . The implementation protocol included a pain assessment workshop and the establishment of a nurse Pain Champion. Quality indicators were tracked before and after implementation. Focus groups and interviews with staff were also conducted. Results . The implementation effort was successful in increasing and regularizing pain assessments. This was sustained during the follow-up period. Staff members reported enthusiasm about the protocol at baseline and positive results following its implementation. Despite the success in increasing assessments, we did not identify changes in the percentages of patients reported as having moderate-to-severe pain. Discussion . It is our hope that our feasibility demonstration will encourage more facilities to improve their pain assessment/management practices. Conclusions . It is feasible to implement regular and systematic pain assessment in LTC. Future research should focus on ensuring effective clinical practices in response to assessment results, and determination of longer-term sustainability.